2015
DOI: 10.1158/2159-8290.cd-15-0819
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metastasis: Perivascular Macrophages Under Watch

Abstract: Summary: TIE2-expressing macrophages cluster around blood vessels and sustain tumor angiogenesis. Harney and colleagues now use live imaging of mouse mammary tumors to show that these perivascular macrophages also promote the transient opening of tumor blood vessels to facilitate hematogenous cancer cell dissemination and metastasis. Cancer Discov; 5(9); ©2015 AACR. See related article by Harney et al., p. 932 (5).Tumors often contain abundant macrophage infi ltrates, which are largely derived from circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Streaming macrophages on the other side do not express these markers, and yet, they can potentially turn into perivascular macrophages expressing TIE2. Indeed, despite the original thought that TIE2 + macrophages may either arise as tissue‐resident macrophages, or from committed TIE2 + monocyte progenitors, there is now strong evidence that hypoxia stimulates TIE2 expression . Furthermore, recent studies have collectively shown that macrophage repolarization in the tumor microenvironment can be achieved by inhibition of the CSF1/CSF1R signaling pathway, and is associated with phenotypic modifications such as activation/enhancement of CD8 + T‐cell mediated immunity and suppression of the angiogenic potential .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Streaming macrophages on the other side do not express these markers, and yet, they can potentially turn into perivascular macrophages expressing TIE2. Indeed, despite the original thought that TIE2 + macrophages may either arise as tissue‐resident macrophages, or from committed TIE2 + monocyte progenitors, there is now strong evidence that hypoxia stimulates TIE2 expression . Furthermore, recent studies have collectively shown that macrophage repolarization in the tumor microenvironment can be achieved by inhibition of the CSF1/CSF1R signaling pathway, and is associated with phenotypic modifications such as activation/enhancement of CD8 + T‐cell mediated immunity and suppression of the angiogenic potential .…”
Section: Discussionmentioning
confidence: 99%
“…Further IHC/IF analyses on TMEM sites have indicated that each functional TMEM site is composed of a perivascular macrophage expressing high levels of TIE2, VEGFA, and mannose receptor (MRC1), suggesting they could represent a distinct subpopulation of M2 or M2‐like TAMs. TIE2 HIGH VEGFA HIGH MRC1 HIGH macrophages have been intensely studied as they can induce pro‐angiogenic, pro‐metastatic, immunosuppressive, and chemoresistant niches in a context‐dependent manner. For example, using the well‐described MMTV‐PyMT mouse model of breast carcinoma, it was demonstrated that VEGFA secreted by the TIE2 HIGH macrophage on TMEM sites disassembles the underlying vascular junction proteins, zonula occludens‐1 (ZO1) and vascular‐endothelial cadherin (VE‐CAD), exposing a paracellular passage that metastasizing tumor cells use to escape into the circulation .…”
Section: Tumor‐associated Macrophages In Cancer Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…Evidences from clinical and experimental studies indicate that macrophages are versatile cells that are capable of displaying different functional activities in order to promote breast cancer progression and metastasis [20, 120, 121]. TAMs polarization in mammary tumor sites are modulated by the tumor microenvironment and these cells are “educated” adopting a role that facilitates angiogenesis, matrix breakdown, and tumor cell motility in a COX-2-dependent manner [71, 105].…”
Section: Inflammatory Cells and Cancer Cell Biomarkersmentioning
confidence: 99%